Frugal supply chains: a managerial and societal perspective. Issue 3 (7th August 2018) - Fulconis, François; Pache, Gilles; Reynaud, Emmanuelle
Abstract : Purpose: The paper aims to introduce the issue of supply chain management in the context of increasingly rare and costly resources and to define the notion of frugal supply chain, in particular, in reference to the development of circular economy. The challenges of frugal supply chain are detailed for a set of private and public stakeholders. Design/methodology/approach: As a programmatic viewpoint, this paper aims at developing debates regarding the future of supply chains, building upon current technical and managerial innovations. Findings: Frugal supply chains constitute a new business perspective. It transforms the way value creation process is considered, in reference to the models of circular economy, and the systems in which companies evolve. The circular economy represents many opportunities for new forms of growth in the context of rare resources, and it raises several challenges for a variety of stakeholders, more or less, involved in the management of closed loop supply chains. Practical implications: Frugal strategies in a supply chain context may provide both a source of competitive advantage for companies and an enhancement of their commitment to society. Social implications: The practices described in the paper aim at stimulating a new view of logistics management, based on the principles of sustainable development. Frugal supply chains offer the possibility of reflecting on a more moderate, sensible and effective use of several commons by taking part in the conservation of rare resources for future generations. Originality/value: This viewpoint introduces the concept of frugal supply chains, rarely approached in the literature, and it offers the opportunity to open debates on managerial and societal challenges linked to logistics strategies and, more broadly, to inter-organizational relations.